Analysis Of The Influence Of Organizational Culture And Competencies On The Performance Of Employees Of The Sinembah Tanjung Muda Hulu Sub-District Office - Dian Utami; Soulthan Saladin Batubara; Firman Ario (International Journal of Management, Economic and Accounting, 2025)
The research analysis aims to analyze the influence of organizational culture and competence on the performance of employees of the Sinembah Tanjung Muda Hulu Sub-district Office. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This study uses multiple linear regression analysis. The sample in this study was 37 respondents. Primary data collection uses questionnaires. The results of the study showed that thetest results for the organizational culture variable showed a t-value of 2.964 > a t-table of 2.03 with a significant value of 0.005 < 0.05, then the H1 hypothesis was accepted and H0 was rejected, meaning that organizational culture had a positive and partially significant effect on the performance of employees of the Sinembah Tanjung Muda Hulu Sub-district Office. The test results for the competency variable showed at-value of 5.161 > a t-table of 2.03 with a significant value of 0.00 < 0.05, then the H2 hypothesis was accepted and H0 was rejected, meaning that competence had a positive and partially significant effect on the performance of employees of the Sinembah Tanjung Muda Hulu Sub-district Office. The results of the simultaneous hypothesis test or F test prove that the value of F is calculated as 71.841 which is greater than 3.28 and the significant value of 0.000 is less than 0.05 so that it can be concluded that H3 is accepted and H0 is rejected so that it can be concluded that organizational culture and compensation have a significant effect simultaneously on the performance of employees of the Sinembah Tanjung Muda Hulu Sub-district Office.